Geological map of the Tocomar Basin (Puna Plateau, NW Argentina): Implication for the geothermal system investigation - Filipovich, Ruben Eduardo (2020)
This paper presents a detailed geological map at the 1:20,000 scale of the Tocomar basin in the Central Puna (north-western Argentina), which extends over an area of about 80 km2 and displays the spatial distribution of the Quaternary deposits and the structures that cover the Ordovician basement and the Tertiary sedimentary and volcanic units. The new dataset includes litho-facies descriptions, stratigraphic and structural data and new 234U/230Th ages for travertine rocks. The new reconstructed stratigraphic framework, along with the structural analysis, has revealed the complex evolution of a small extensional basin including a period of prolonged volcanic activity with different eruptive centres and styles. The geological map improves the knowledge of the geology of the Tocomar basin and the local interplay between orogen-parallel thrusts and orogen-oblique fault systems. This contribution represents a fundamental support for in depth research and also for encouraging geothermal exploration and exploitation in the Puna Plateau region